The Role of Inventory Accounting Information Systems in Supporting The Effectiveness of Internal Control Inventory - Uswandi Uswandi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
In general, in a company it is necessary to manage all adequate resources for its various activities. So as to achieve the company's operating goals, namely efficiency (minimum expenditure of resources) and effectiveness (achieving desired results). In general, each company has an accounting information system, each of which is adjusted to the scope of business activities, conditions, and company needs. An accounting information system was created to identify, classify, analyze, record, and report transactions from business units. Based on this consideration, this research was conducted to find out how the implementation of inventory accounting information systems to support the effectiveness of internal inventory control on the CV. Mulia Raya Prima in Bandung. The method that will be used in this research is descriptive method that is by emphasizing the observation (observation) related activities that occur in the company CV. Noble Raya Prima. In order to obtain a picture of the facts and properties that support each other between the inventory accounting information system with internal inventory control, then analyze the results of the study by making a comparison (comparison) of standards applied by the company (through interviews with the leaders of CV. Mulia Raya Prima with the circumstances actually what happens is based on observations. Based on the results of research on the role of inventory accounting information systems on the effectiveness of internal inventory control, it is known that the inventory accounting information system applied to CV. Mulia Raya Prima is quite effective in supporting inventory internal control. The company also has an internal oversight unit which is added by supervision from the company's leadership which is quite good.